2017
DOI: 10.1051/matecconf/201713805007
|View full text |Cite
|
Sign up to set email alerts
|

Using BIM as a Tool to Teach Construction Safety

Abstract: Abstract. The advancement of computer technology allows the construction education to exploit the various teaching strategies. Unlike other engineering subjects, teaching construction subjects often requires media beyond traditional class room environment that would enable the creation of field-like construction atmosphere. Construction visualization allows students to exercise and experience various field settings that are too difficult to deliver using traditional teaching approach. This paper aims at descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Irizarry et al [134] also revealed that the supply chain is arranged in a better precise, efficient, and cost-effective method with the integration of BIM and geographic information systems (GIS). From the perspective of safety management and planning, through BIM 4D's simulation and visualization of the green building construction progress, BIM can conduct risk identification and safety training for management personnel and construction workers [135][136][137][138][139]. Moreover, through the BIM 4D hazard identification component established by Heidary et al [140], BIM can assist green building construction managers in identifying and demonstrating the potential construction hazards in the early stages of green building projects [140].…”
Section: Planning and Schedule Management Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Irizarry et al [134] also revealed that the supply chain is arranged in a better precise, efficient, and cost-effective method with the integration of BIM and geographic information systems (GIS). From the perspective of safety management and planning, through BIM 4D's simulation and visualization of the green building construction progress, BIM can conduct risk identification and safety training for management personnel and construction workers [135][136][137][138][139]. Moreover, through the BIM 4D hazard identification component established by Heidary et al [140], BIM can assist green building construction managers in identifying and demonstrating the potential construction hazards in the early stages of green building projects [140].…”
Section: Planning and Schedule Management Optimizationmentioning
confidence: 99%
“…Moreover, In BIM 4D, the stakeholders can become familiar with the conditions of buildings at different periods through visual 3D demonstrations [100,[117][118][119][120][121][122]142,143,145,164]. From the perspective of safety management, BIM's visualization can assist construction teams in identifying the clashes and potential risks in a visual manner, so as to provide the corresponding safety training and avoid delay, construction waste production, and rework [5,14,46,99,133,135,136,[138][139][140].…”
Section: Bim Utilization In the Green Building Construction Phasementioning
confidence: 99%